Implementasi Green Human Resource Management dalam Meningkatkan Corporate Sustainability pada Perusahaan di Cikarang, Indonesia - Fardhal Virgiawan Ramadhan; Ade Chaerul (Jurnal Riset Ekonomi dan Akuntansi, 2023)
Green human resource management (GHRM) is a practice used to protect the surrounding environment by creating a sustainable culture. GHRM can be carried out in various dimensions including green recruitment and selection, green job analysis and design, green training, and development, green performance management, and green reward management. Of course, this is in accordance with the sustainability of the company or the sustainability of companies that have direct social responsibility towards society and the environment. The purpose of this study is to explain the implementation of GHRM on corporate sustainability in Cikarang companies, Indonesia. This study used a qualitative descriptive-analytical research method by observing 37 respondents at a Cikarang company, in Indonesia. The results of this study indicate that companies in Cikarang, Indonesia have started implementing GHRM aspects which focus on environmentally friendly practices of green recruitment and selection, green job analysis and design, green training, and development, green performance management, and green reward management. The application of GHRM certainly helps companies find employees who have awareness and commitment to sustainability issues.